Express methods for determining oil weight fraction in vegetable lecithins based on the pulse method of nuclear-magnetic resonance - E. P. Victorova; G. V. Rusnak; T. A. Shakhray; O. S. Agafonov; S. M. Prudnikov (Новые технологии, 2017)
Express methods for determining oil weight fraction in vegetable lecithins (sunflower, soybean, and racial) based on the pulse nuclear magnetic resonance method have been developed, which have a number of advantages compared with arbitration method, namely, the use of toxic organic solvent (acetone) is excluded, i.e. these methods are environmentally safe, the analysis time is significantly reduced (instead of 10 hours) - 5 minutes, that is, these are express methods and qualification requirements to laboratory personnel are also reduced, since the process of performing the analysis is automated.